CURRENT PATTERN OF HEART DISEASE COMPLICATING PREGNANCY IN A SRI LANKAN UNIT - Kaluarachchi, A; De Alwis, D; Gnanasekeream, R; Gunawansa, N; Wijeratne, C; Seneviratne, H R (My University, 2012)
Introduction: Our unit has been studying the changing pattern of heart disease over the past five decades. Although there is a relative decrease in the incidence of rheumatic heart disease in developing countries, the advancement of facilities for cardiac investigations has lead to the increase in the diagnosis of cardiac lesion. Objectives: To study the current pattern of heart disease. Study Design : Retrospective descriptive study. Setting: University Obstetric Unit, De Soysa Hospital for Women, Colombo. Method : Data collected from the records of 152- consecutive mothers with heart disease who delivered during the period from 01/09/98 to 30/11/00. Results : 46%(n=70) had rheumatic valvular disease, 30%(n=45) had congenital heart disease and 24%(n=37) had Mitral Valve Prolapse. MS-MR (45.7%) and MS (34.2%) were the leading cardiac pathologies in the category of rheumatic heart disease. ASD (57.8%) and VSD (28.9%) were the main congenital lesions. Two maternal deaths due to heart disease complicating pregnancy were recorded during this period. The ratio between congenital heart disease and rheumatic heart disease was 1:1.55, compared to 1:1.54(1993-1994), 1:1.93(1989-1992),1:4.11(1974- 1977),1:3.37(1965-1967) and 1:2.1(1950-1952). Conclusion : Heart disease complicating pregnancy, both rheumatic and congenital in origin is a significant problem in obstetric practice. The change in trend observed in 1993-94 is maintained though there appears to be a slight increase in rheumatic heart disease.